Translocal Mobilization of Housing Commons. The Example of the German Mietshäuser Syndikat - Hölzl, Corinna (Frontiers in Sustainable Cities, 2022)
We are currently observing an international trend towards the establishment of nonprofit-oriented, collaborative and self-managed housing models. In this respect, knowledge concerning commoning has been circulating globally with initiatives mutually interacting. This is also true for the Mietshäuser Syndikat, which by now comprises some 170 permanently decommodified houses in Germany and has been transferred to the legal spaces of several neighboring states (Austria, France, Netherlands, and Czech Republic). Against this background, this paper addresses the question of how housing commons such as the Syndikat circulate translocally and what role spatial learning processes and network dynamics play in that regard. Conceptually, the study refers to the spatialities of social movements. Participatory observations at (inter-)national meetings as well as network graph-assisted interviews with key actors of the Syndikat model represent the central methods of the study. The findings illustrate that (1) solidary knowledge transfers via key actors who take on advisory and network functions, (2) open physical and (3) virtual meeting points facilitate a moderate diffusion and permanent adaptations of the housing commons model. A process of “assembling, dis-assembling, re-assembling along the way” (McCann and Ward 2012) thus unfolds. However, the findings illustrate that these mechanisms are not strong enough to compensate unequal relations of power and resources – among other in view of local pre-conditions.